The Two Faces of TASS - Kruglak, Theodore Eduard (Book collections on Project MUSE., 1962)
The Two Faces of TASS was first published in 1962. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. What is TASS and how does it operate? As the Soviet Union's international news agency does TASS serve other purposes besides the gathering and distribution of news? Does it engage in espionage? In propaganda? This account of the development of TASS and analysis of its present-day operations provides illuminating answers to such questions as these in a book that is significant not only to communications specialists but to anyone who wants to understand Soviet relations with the rest of the world. Mr. Kruglak sketches the historical background of TASS and its antecedents and gives fascinating sidelights on the men who made TASS. He shows the evolution of the agency to its present status, explains its relationship to the news agencies of the various Soviet Republics and satellite countries, and recounts the relations of TASS and its predecessors with American news agencies. Journalism educators will be especially interested in the chapter on the training of Soviet journalists and the discussion of the TASS concept of news. There is a comprehensive discussion of TASS operations in the United States and a detailed analysis of the TASS treatment of news of this country. The TASS handling of news from 33 other countries is examined and compared with the New York Times treatment of such news for the same period. Similarly, TASS reports of the news of the Soviet Union are analyzed. Finally, the questions of espionage and propaganda roles are discussed. In conclusion, the author points to the need for "news communication coexistence" between the U.S.S.R. and the rest of the world, and suggests that news media lead the way to an approach to international understanding